In India, Inclusive Education Is Global Idea with a National Meaning (International Journal of Innovative Research in Engineering & Management, 2023)
In the context of India, this article looks at  the education of children from marginalized communities,  with a focus on children with incapacities. Various  educational arrangements for the children with incapacities are addressed based on an examination of post independences government papers. It delves into the  Indian government's attempts to establish special schools,  as well as its integration initiatives and more current prominence on comprehensive education. It also tries to  define "inclusive education" as it is defined in different  government publications. The essay ends by stating that a  contextual knowledge of inclusive education is required in  order to address India's present educational problems. In  1947, the year India gained independence, the Indian  Constitution included education as a guiding idea rather  than a basic right. While everyone has basic human rights  and freedoms, which take precedence above any other  legislation of the place, directive concepts are said to be  important in the workings of government but are not  legally valid.
Keywords: Disability; Education; Global Idea; Inclusive Education; Indian Education